Tamara Levitz, Modernist Mysteries: Perséphone (2012) - Walsh, Stephen (Journal of the Society for Musicology in Ireland, 2014)
A review of Tamara Levitz, Modernist Mysteries: Perséphone (Oxford: Oxford University Press, 2012). ISBN 978-0-1997-3016-2.